Analysis of the thermal behavior of self-written waveguides. (April 2022) - Günther, Axel; Baran, Murat; Garg, Roopanshu; Roth, Bernhard; Kowalsky, Wolfgang
Abstract: Photonic elements are among the key components of various integrated systems for measurement, sensing and data transmission. Thus, to realize more complex systems, connecting different such elements reliably with each other gains more and more interest. Self-written waveguides (SWWs) represent a promising class of optical interconnects and might, in addition, even be suited for further functional applications. Here, we investigate the thermal behaviour of SWWs and demonstrate that a change in temperature can be detected with an SWW-connected fiber by monitoring the transmitted light only. In contrast to the usual behaviour of polymers, we find conditions where the transmitted intensity through the SWW increases as the temperature is raised which is counter-intuitive. By studying the thermal behaviour of SWWs, we create a firm basis for their potential use as simple, robust and versatile sensing elements in the future.